The performance impact of gender diversity in the top management team and board of directors: A multiteam systems approach - Wu, Jie; Richard, Orlando C.; Triana, María del Carmen; Zhang, Xinhe (Human Resource Management, 2022)
Given the mixed evidence that having both women and men in the top management team (TMT) or in the board of directors (BOD) has a significant influence on organizational innovation, we resolve this issue by conceptualizing TMT–BOD gender diversity as part of a multiteam system, that has joint effects which impact organizational innovation. Evidence from the study of both Chinese firms and UK firms confirm our conceptualization by showing an interaction effect between TMT gender diversity and BOD gender diversity such that innovation is greatest when both are high. The positive TMT–BOD gender diversity interaction effect on innovation improves subsequent firm performance particularly in dynamic environments. The findings refine current thinking by going beyond research that tests intra‐team TMT or BOD diversity independently and instead considers inter‐team diversity across both leadership teams within the strategic leadership upper echelons. In sum, findings show that high levels of TMT and BOD gender diversity result in more organizational innovation, which ultimately improves firm performance. We offer implications for women's inclusion in leadership as well as for research on the upper echelons.